Performance prediction and working fluids selection for organic Rankine cycle under reduced temperature. (5th May 2019) - Chen, Guibing; An, Qingsong; Wang, Yongzhen; Zhao, Jun; Chang, Nini; Alvi, Junaid
Highlights: A theoretical exergy efficiency model is derived for subcritical ORC. Working fluid gains maximum exergy efficiency when Ths, in approaches to its Tcri . The exergy efficiencies of different fluids are equal on same reduced temperatures. The optimal dimensionless evaporating temperature is given. Abstract: This paper presents the approach for selection of optimal working fluids and cycle performance prediction for organic Rankine cycle (ORC) based on a theoretical exergy efficiency model (EEM) under reduced temperature. 18 working fluids with critical temperature from 100 to 200 °C are under evaluation. When the condensing temperature is 40 °C and reduced evaporating temperature is 0.85, the maximum overall exergy efficiency will be obtained when the heat source temperature approaches to the critical temperature of working fluid. Then, the optimal working fluids are selected by overall exergy efficiency. When the heat source inlet temperatures are 130 °C, 150 °C, 170 °C and 190 °C, the optimal working fluids are R236ea, R245fa, R245ca and R365mfc, respectively. In addition, under the same entire reduced temperatures the exergy efficiencies of different working fluids tend to be approximately equal and obey the circular distributions. The quantitative correlation between the optimal reduced evaporating temperature and reduced heat source temperature is given. The correlation provides a non-dimensional method to calculate the optimal evaporating temperature for different working fluids on the target of exergy efficiency.